Acquisition and Analysis of Cognitive Evoked Potentials using an Emotiv Headset for ADHD Evaluation in Children (2019)
Attention-deficit/hyperactivity disorder (ADHD) is a neurological condition that affects the quality of life of the patients. It can be diagnosed using a combination of psychological tests. In addition to that, the brain activity of the patients can be analyzed using electroencephalography (EEG). The application of EEG tests requires the cooperation of the patients, which can be challenging in patients with ADHD. This paper describes the development of a system for stimuli generation, and acquisition and analysis of cognitive evoked potentials using the commercial system Emotiv EPOC+ headset. The results show that the system allows precise and reliable measurements of the P300 waves in children, and may provide a more comfortable experience for the patients compared to medical-grade systems. © 2019 IEEE.